Structural and functional model of formation of readiness of future specialists in computer technologies for professional activity by means of digital technologies - Lesia Hiltai (Kazimierz Wielki University, 2022)
The article substantiates the structural and functional model of formation of the readiness of future specialists in computer technologies for professional activity by means of digital technologies. To achieve the goal of the article, the methodology is applied, which consists in conducting an analysis of the research of the problem of pedagogical modeling of the formation of the readiness of future specialists in computer technologies for professional activities in the field of digital technologies. On the basis of the conducted analysis, the concept of «structural-functional model», its structure and prospects of introduction into the educational process of future specialists in computer technologies are defined. It has been established that models in pedagogical science are successfully used for high-quality planning of the educational process, management of cognitive activity of students and optimization of the structure of educational material. In order to build a structural-functional model, its main constituent elements were determined, combined into logical blocks corresponding to the stages of the educational process (target, content, organizational, diagnostic-resultative) and complex application of modern digital technologies at all stages. The effectiveness of the implementation of the model was ensured by predefined organizational and pedagogical conditions.